2022
DOI: 10.3389/fendo.2022.1032499
|View full text |Cite
|
Sign up to set email alerts
|

Protein O-GlcNAcylation as a nutrient sensor signaling placental dysfunction in hypertensive pregnancy

Abstract: IntroductionDuring pregnancy, arterial hypertension may impair placental function, which is critical for a healthy baby's growth. Important proteins during placentation are known to be targets for O-linked β-N-acetylglucosamine modification (O-GlcNAcylation), and abnormal protein O-GlcNAcylation has been linked to pathological conditions such as hypertension. However, it is unclear how protein O-GlcNAcylation affects placental function and fetal growth throughout pregnancy during hypertension.MethodsTo investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Fetal growth is a continuous process in which cells, tissues, and organs differentiate and undergo maturation. During this process, the transport of primary nutrients, such as glucose, amino acids, and lipids, is essential for the development of a healthy baby ( 11 ). The placenta not only maintains the pregnant state and protects the embryo from infection, but also promotes the exchange of nutrients, gases, and waste products so that the embryo can safely survive and grow in a healthy intrauterine environment ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fetal growth is a continuous process in which cells, tissues, and organs differentiate and undergo maturation. During this process, the transport of primary nutrients, such as glucose, amino acids, and lipids, is essential for the development of a healthy baby ( 11 ). The placenta not only maintains the pregnant state and protects the embryo from infection, but also promotes the exchange of nutrients, gases, and waste products so that the embryo can safely survive and grow in a healthy intrauterine environment ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…This condition may lead to fetal growth restriction and fetal hypoxia, and in severe cases, irreversible ischemic organ damage and intrauterine fetal death may occur ( 13 ). Recent study findings suggested that insufficient placental nutrition transport during hypertensive pregnancy impairs fetal growth by decreasing placental protein O-GlcNAcylation ( 11 ). The proper functioning of the placenta depends on the integrity of its structure, which involves trophoblasts, immune cells and other placental cells proliferating, differentiating, and undergoing apoptosis at proper rates and in a balanced state.…”
Section: Introductionmentioning
confidence: 99%